2004
DOI: 10.1111/j.1398-9995.2004.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the treatment of atopic eczema/dermatitis syndrome in infants: a double‐blind placebo‐controlled trial

Abstract: Treatment with LGG may alleviate AEDS symptoms in IgE-sensitized infants but not in non-IgE-sensitized infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
315
2
18

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(358 citation statements)
references
References 34 publications
8
315
2
18
Order By: Relevance
“…Numerous studies support the beneficial effect of living microbial food supplements in health and disease (Marcos et al, 2004;Valeur et al, 2004;De Vrese et al, 2005;Viljanen et al, 2005;Weston et al, 2005;Ewaschuk and Dieleman, 2006;Olivares et al, 2006;Suomalainen et al, 2006). The functional properties of probiotics are strainspecific.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies support the beneficial effect of living microbial food supplements in health and disease (Marcos et al, 2004;Valeur et al, 2004;De Vrese et al, 2005;Viljanen et al, 2005;Weston et al, 2005;Ewaschuk and Dieleman, 2006;Olivares et al, 2006;Suomalainen et al, 2006). The functional properties of probiotics are strainspecific.…”
Section: Introductionmentioning
confidence: 99%
“…shermanii) did not have a signifi cant effect. 131 Interestingly, the same four probiotics given in combination with a prebiotic reduced the incidence of eczema and atopic eczema and tended to reduce IgEassociated diseases overall in a primary prevention trial. 124 This may suggest that probiotics have different effects in developing compared with in established disease.…”
Section: Probiotics In Allergic Diseasesmentioning
confidence: 99%
“…Others were unable to detect signifi cant differences in the group overall, but found the LGGassociated improvements to be signifi cant in subgroups of children with IgE-associated disease. 131 In the same study, a combination of four probiotics (LGG, L. rhamnosus LC705, B. breve Bb99, and Propionibacterium freudenreichii ssp. shermanii) did not have a signifi cant effect.…”
Section: Probiotics In Allergic Diseasesmentioning
confidence: 99%
“…The age range of subjects included varies between studies: around weaning (median 5 months old) (Brouwer et al, 2006;Isolauri et al, 2000;Kirjavainen et al, 2003;Viljanen et al, 2005b;Gruber et al, 2007), around 1 year old (Weston et al, 2005;Folster-Holst et al, 2006), and around 5 years old (Rosenfeldt et al, 2003(Rosenfeldt et al, , 2004Sistek et al, 2006;Woo et al, 2010). Seven of these publications describe effects of Lactobacillus rhamnosus GG LGG in infants but report contradictory results (Brouwer et al, 2006;Isolauri et al, 2000;Kirjavainen et al, 2003;Viljanen et al, 2005b;Gruber et al, 2007;Folster-Holst et al, 2006;Nermes et al, 2011). Two of them (Isolauri et al, 2000;Kirjavainen et al, 2003) showed a significant decrease of the SCORAD score, but both these studies included only small groups of infants (27 and 35).…”
Section: Clinical Impact Of Probiotics In Atopic/allergic Diseases 4mentioning
confidence: 99%